Percepción de la población sobre los puntos de acumulación de residuos sólidos municipales en San Juan Bautista - 2021 - Grandez Villasis, Ambar Yliana (2022)
This work was carried out in the district of San Juan Bautista, Maynas Province, Loreto Region, where 50% of 344 homes were evaluated for convenience. It is concluded that 48% of the interviewees have secondary education and 36% higher education. Regarding the physical perception of the population, the Plaza Colinas accumulation point reflects a greater accumulation of waste, 64% say that it causes them annoyance and 3% respond that they never have. 77% responded that accumulation causes bad odors and 1% say never, which shows that a large percentage perceive this discomfort, and that this attracts the presence of scavengers (60%), and also the presence of rodents and flies (49%). When evaluating emotional perception, 63% of people are always and many are emotionally upset by the presence of solid waste, however, 11% say they are never upset. That is why it is important to highlight that 42% always face changes in their lives and 16% say they never, so awareness and environmental education about solid waste San Juan Bautista should be implemented.